Polylactide-Based Materials: Synthesis and Biomedical Applications - Brzeziński, Marek; Baśko, Małgorzata (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on PLA-based materials and the modification of their properties for biomedical applications. Special emphasis is placed on the supramolecular strategies that lead to unique structures in the micro- or nanoscale. The development and testing of novel biomaterials as drug delivery carriers, implants, or tissue engineering scaffolds are of particular interest. Special attention is given to understanding the structure-properties relationship, since this allows for the development of the most effective biocompatible materials.